Dampak Cuci Tangan Pakai Sabun Terhadap Kasus Diare di Desa Sumi Kecamatan Lambu Kabupaten Bima - Mujiburrahman Mujiburrahman (Universitas Katolik Widya Karya Malang, 2023)
Diarrhea is an endemic disease in Indonesia and is also a potential illness of outbreaks that is often accompanied by death. This study aims to determine the effect of clean water sources, handwashing behavior with soap and the use of healthy latrines.The design of this research is observational analytic research using cross sectional approach. The population in this study is the head of the family in the neighborhood of Sumbawa Village, Tanjung Sub-District, Rasanae Barat Kota Bima, which amounts to 673 families. The sample in this study was 249 HH obtained by using simple random sampling technique and in the analysis by using multiple logistic regression test. The results of this study are all variables of this study meaningful, namely: the source of clean water effect on the occurrence of diarrhea (p value = 0,000 <0.05), handwashing behavior with soap has an effect on the occurrence of diarrhea (p value = 0,000 <0,05) Healthy latrines have an effect on the occurrence of diarrhea (p value = 0.002 <0.05). Conclusion in this research: 1) There is influence of source of clean water. 2) there is influence of handwashing behavior with soap. 3) the use of healthy latrines. Suggested: 1) For health service to make policy about PHBS and provide water absorbent tool called Water Softener. 2) For puskesmas to improve the extension of PHBS. 3) For kelurahan to make health program about PHBS and submit to health service. 4) For the community to want to apply PHBS to prevent the occurrence of disease, especially diarrhea diseases. 5) For other researchers need further research with research design and different variables to know other factors that affect the occurrence of diarrhea.